The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/699173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human induced pluripotent stem cell-derived neuroectodermal epithelial cells mistaken for blood-brain barrier-forming endothelial cells

Abstract: 33Brain microvascular endothelial cells (BMECs) possess unique properties 34underlying the blood-brain-barrier (BBB), that are crucial for homeostatic brain functions 35 and interactions with the immune system. Modulation of BBB function is essential for 36 treatment of neurological diseases and effective tumor targeting. Studies to-date have 37 been hampered by the lack of physiological models using cultivated human BMECs that 38 sustain BBB properties. Recently, differentiation of induced pluripotent stem ce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…1b). TAL1 rapidly strengthened the barrier properties of ECs and TAL1 is reported to be involved in EC specification 46 . LYL1, a close homolog in TAL1, may be to be critical for generating the barrier in lung ECs.…”
Section: Discussionmentioning
confidence: 96%
“…1b). TAL1 rapidly strengthened the barrier properties of ECs and TAL1 is reported to be involved in EC specification 46 . LYL1, a close homolog in TAL1, may be to be critical for generating the barrier in lung ECs.…”
Section: Discussionmentioning
confidence: 96%
“…A very recent publication by Raphael Lis and collaborators [50] had raised doubts about the endothelial nature of in vitro BBB models derived from neuroendothelial differentiation of iPSC by opposition to the mesoendothelial differentiation, mainly on a transcriptome-based analysis. They reported that cells derived using neuroendothelial differentiation lack canonical endothelial markers such as VE-CADHERIN and PECAM1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite instances where the hPSC-derived BMECs were differentiated through vastly different methods (for example, the co-differentiation process [1] versus a transition through a mesodermal progenitor state [6]), RNA sequencing techniques indicate that these cells share similar global transcriptional profiles [6]. However, transcriptomic analyses have also revealed an unexpected feature of these BMECs in that they express a substantial number of epithelial-associated transcripts [9,20,21]. Given that this particular issue is of significant interest to the BBB community, we detail the endothelial and epithelial attributes of hPSC-derived BMECs and provide our perspective on current strengths and weaknesses that should be considered when deploying hPSC-derived BMECs in a research setting, and areas that need to be improved with further model refinement.…”
Section: Introductionmentioning
confidence: 99%